Phylogenetics and population genetics tools for vectors and vector-borne pathogens: COST Action EurNegVec, Training School 6 - salgueiro, P. (Anais do Instituto de Higiene e Medicina Tropical, 2018)
Phylogenetics and Population Genetics provide knowledge on ecological and evolutionary processes significant to vector-borne diseases, through the analysis of spatial and temporal patterns of genetic variation in arthropod vectors and their pathogens. The Centre for Global Health and Tropical Medicine (GHTM) / Institute of Hygiene and Tropical Medicine (IHMT) hosted an international Training School on “Phylogenetic and population genetics tools for vectors and vector-borne pathogens” (TS6), within the COST Framework EurNegVec (the European Network for Neglected Vectors and Vector-Borne Infections BMBS COST Action TD1303).The main aims of the Training School were to help the trainees to: 1) learn the basic principles of phylogenetics and population genetics studies; 2) understand the implications of such studies for the surveillance and control of vector-borne diseases; 3) to train on several dedicated software. In this paper we present a synopsis of this one-week Training School, of its main contents and participants.